Paleoambientes quartenários da planície do Ria Iapó. Castro, Paraná - Kalinovski, Elaine Cristina Zavadovski (2015)
The research proposed to characterize the paleoenvironmental conditions in the flood plain of the Iapó River, from a sedimentary testimony obtained on the left margin of the river, located near the urban area of Castro, in the Central-East region of Paraná State and encompassing the landscape unit of Campos Gerais. Thus, we emphasize the use of different proxies data (multiproxy analysis) as spicules of continental sponges and phytoliths, ssociated with the determination of the isotopic values of δ13C, δ15N, C/N ratio and absolute dating (14C), for the correlation, great detailing and accuracy of the relevant information to the environmental variations or changes in the study area during the time interval which refers to the Quaternary. For the extraction and recovery of silica from biogenic microfossils compounds present in the sediment samples, it was applied standard methodology used in palynology which consists in heating with potassium hydroxide (10%) and zinc chloride suspension. It was possible identification of gemoscleras preserved in sedimentary deposit, of taxa of freshwater sponges from lotic and lentic, and detection of live exemplary of Oncosclera schubarti Bonetto and Ezcurra Drago, 1967 stuck in the bedrock riverbed Iapó. The absolute dating (14C) operated on the basis of the testimony, which is 114 cm deep, revealed age dating back to the Late Pleistocene, 18.371 years with lime. BP., while about 70 cm timing obtained was 2.006 cal. years. BP. on the Late Holocene. Results showed: i) active channel phase for at least 18.000 years BP., developed initially through the open vegetation domain C4 cycle plants; ii) channel abandonment phase and beginning of the formation of an abandoned meander, with deposits related to the evolution of bars in point, covered with vegetation; iii) paleoclimatic conditions similar to the current in the region, with the resumption of moisture in plain and disturbance by flood pulses, showing the retraction of the vegetation of grasses and tree and shrub development, from 2.006 years cal. BP to the present.